Digital interventions for hypertension and asthma to support patient self-management in primary care: the DIPSS research programme including two RCTs - Yardley, L; Morton, K; Greenwell, K; Stuart, B; Rice, C; Bradbury, K; Ainsworth, B; Band, R; Murray, E; Mair, F; May, C; Michie, S; et al. (NIHR Journals Library, 2022)
Background Digital interventions offer a potentially cost-effective means to support patient self-management in primary care, but evidence for the feasibility, acceptability and cost-effectiveness of digital interventions remains mixed. This programme focused on the potential for self-management digital interventions to improve outcomes in two common, contrasting conditions (i.e. hypertension and asthma) for which care is currently suboptimal, leading to excess deaths, illness, disability and costs for the NHS.